Study on the extraction of fulvic acid from lignite by microwave-assisted hydrogen peroxide. (2018) - Zhang, Ao; Zhang, Ying-Jie; Zheng, Hong-Lei; Ma, Lu-Lin; Liu, Wen-Jing; Gong, Guan-Qun
Extraction of fulvic acid (FA) from Hulun Buir (HB) lignite were carried out under the conditions of hydrogen peroxide and microwave-assisted hydrogen peroxide. The results showed that the microwave can greatly improve reaction rate and observably shorten reaction time, while the extraction yield of FA increased around 4%. Purification technology of FA was studied by sulfuric acid-acetone aqueous solution, and then structure of purified FA was evaluated. All results demonstrated that under the assistance of microwave, the oxidative degradation ability of hydrogen peroxide is stronger, the solvent gets higher permeation ability and the oxygen content in FA is higher. Among the oxygenic functional groups of FA, carboxyl group has the highest content, followed by hydroxyl group and the ester content is the lowest. Trisubstituted benzene is the major component in the aromatic structure of FA. In aliphatic structure, content of methylene is the highest. [Received: March 4, 2017; Accepted: October 17, 2017]